PROGRAM WONDERFUL INDONESIA DALAM MENARIK WISATAWAN JEPANG - Faza Raksa Barliana (Universitas Komputer Indonesia, 2017)
This research aims to determine the efforts of the Indonesian government program through Wonderful Indonesia on enhancement Japanese tourists in 2011 until 2015. Background of problems that arise in this research is the what cooperation program undertaken by the government of Indonesia through Wonderful Indonesia against Japanese tourists, whatever constraints must be faced by the Wonderful Indonesia program in bringing tourists from Japan and how the prospects of this program in the future against Japanese tourists.